THE COSMETIC OUTCOME OF BREAST RECONSTRUCTION: REPRODUCIBILITY OF DIFFERENT METHODS ASSESSED BY DIFFERENT PROFESSIONALS - Freitas-Junior, Ruffo; Bayeh, Hugo Andrade; Paulinelli, Regis Resende; Soares, Leonardo Ribeiro; Prates, Ana-Carolina Lagos; Morais, Pauline Camargo; Albuquerque, Izabela Cristina Souza de; Souza, Aloisio Garcia; Beloti, Tuanny Roberta (Mastology, 2019)
Objective: To compare the reproducibility of different methods for assessing the cosmetic outcome of breast reconstruction, which was assessed by different health professionals. Methods: Photographs of 270 breast cancer patients who had been submitted to breast reconstruction of some type were included. A plastic surgeon, a resident in plastic surgery, two mastologists, two residents in mastology, and two psychologists performed the evaluation. The modified Garbay and Harvard scales and the objective BCCT. core software program were used. Cohen’s Kappa and Spearman correlation coefficients were calculated. Results: The mean age of the patients was 55.7 (±11.1) years. Overall, 145 women (53.7%) underwent partial breast reconstruction and 125 (46.3%), total breast reconstruction. The mean follow-up time was 63.7±45.6 months. By applying the Harvard scale, the interobserver reproducibility among the different professionals was minimal; whereas the Garbay scale had no agreement. The correlations between the BCCT.core software program and the Harvard and modified Garbay scales were moderate. Conclusion: Correlations between both the modified Garbay scale and the Harvard scale and the objective (BCCT.core) test were moderate. There was less interobserver variability with the Harvard scale compared to the modified Garbay scale.